Sodium Tanshinone IIA Sulfonate as a Potent IDO1/TDO2 Dual Inhibitor Enhances Anti-PD1 Therapy for Colorectal Cancer in Mice - Zhang, Rongjie; Wang, Yuanfeiyi; Liu, Dan; Luo, Qing; Du, Peixin; Zhang, Haiyan; Wu, Wenshuang (Frontiers in Pharmacology, 2022)
Although the antitumor efficacy of immune checkpoint blockade (ICB) has been proved in colorectal cancer (CRC), the results are unsatisfactory, presumably owing to the presence of tryptophan metabolism enzymes indoleamine 2,3-dioxygenase 1 (IDO1) and tryptophan 2,3-dioxygenase 2 (TDO2). However, only a few dual inhibitors for IDO1 and TDO2 have been reported. Here, we discovered that sodium tanshinone IIA sulfonate (STS), a sulfonate derived from tanshinone IIA (TSN), reduced the enzymatic activity of IDO1 and TDO2 with a half inhibitory concentration (IC50) of less than 10 μM using enzymatic assays for natural product screening. In IDO1- or TDO2- overexpressing cell lines, STS decreased kynurenine (kyn) synthesis. STS also reduced the percentage of forkhead box P3 (FOXP3) T cells in lymphocytes from the mouse spleen cocultured with CT26. In vivo, STS suppressed tumor growth and enhanced the antitumor effects of the programmed cell death 1 (PD1) antibody. Compared to anti-PD1 (α-PD1) monotherapy, combined with STS had lower levels of plasma kynurenine. Immunofluorescence suggested that STS decreased the numbers of FOXP3+ T cells and increased the numbers of CD8+ T cells in tumors. Flow cytometry analysis of immune cells in tumor tissues demonstrated an increase in the percentage of tumor-infiltrating CD8+ T cells. According to our findings, STS acts as an immunotherapy agent in CRC by inhibiting both IDO1 and TDO2.